Kambiyo senetlerinde temsil - Yıkar, Mehmet Emin (My University, 2020)
Kambiyo senetleri, TTK m. 671 ve devamında düzenlenmektedir. Kambiyosenetleri; poliçe, bono ve çekten oluşmaktadır. Bu senetler, ödeme, kredi ve teminat aracıolarak kullanılmaktadır. Günlük yaşamda yaygın biçimde kullanılan kambiyo senetleri,temsilci aracılığıyla işlem görebilmektedir.Kambiyo senetlerinde temsile ilişkin tek hüküm, yetkisiz imza kenar başlıklı TTKm. 678’dir. Hükümde, temsil yetkisinin aşılması veya bulunmaması halinde temsilcininsorumluluğu düzenlenmektedir. Kambiyo senetlerinde temsile ilişkin diğer hususlar iseTTK’da yer almamaktadır. Bu nedenle TBK’nın temsile ilişkin genel hükümleri,niteliklerine uygun olduğu ölçüde kambiyo senetlerinde temsile uygulanmaktadır.Çalışmamızda, kambiyo senetlerinde temsilin kolay anlaşılabilmesi için öncelikleTBK’nın temsile ilişkin genel hükümleri ele alınmıştır. Çalışmamızın ileryeyenkısımlarında, uygulama ile bağlantının kurulabilmesi amacıyla, yüksek mahkemeiçtihatlarından da faydalanılarak, kambiyo senetlerinde temsilci aracılığıylagerçekleştirilebilen işlemler, bu işlemlerin yapılma biçimleri ve kambiyo senetlerindeyetkisiz temsil hali incelenmiştir.

Bills of exchange are regulated in Article 671 of the Turkish Commercial Code no6102 and its continuation. Bills of exchange; consists of notes, bills and cheques. Thesebills are used as a means of payment, credit and guarantee. Bills of exchange, which arewidely used in daily life, can be traded through a representative.The only provision regarding representation in bills of exchange is Article 678 ofthe Turkish Commercial Code titled unauthorized signature. In the provision, theresponsibility of the representative is regulated in the event that the authority ofrepresentation is exceeded or absent. Other issues regarding representation in bills ofexchange are not included in the Turkish Commercial Code. For this reason, the generalprovisions of the Turkish Code of Obligations on representation apply to representationin bills of exchange to the extent that it is appropriate for its natur.In our study, in order to make the representation in bills of exchange easy tounderstand, firstly, the general provisions of the Turkish Code of Obligations regardingrepresentation were discussed. In the later parts of our thesis, transactions that can becarried out through representative in the bills of exchange, the methods of thesetransactions and unauthorized representation in the bills of exchange are examined byusing case law of High Courts in order to establish connection with the application.
Keywords: Bills of exchange; billsof exchange transactions; Civil law; kambiyo işlemleri; Kambiyo senetleri; Medeni hukuk; representation; temsil; unauthorized representation; yetkisiz temsil